ANÁLISE COMPARATIVA DE TÉCNICAS DE FILTRAGEM ESPACIAL EM ÁREA RURAL NA REGIÃO DO MÉDIO ALTO URUGUAI – RS - Piazza, Eliara Marin; Mariano, Lílian Gonçalvez; Hummel, Rafaela Badinelli; Felker, Roselene Marostega; Coghetto, Franciele; Stefanello, Maureen de Moraes (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
The image filtering is a technique used to improve the quality of digital images through the incorporation of algorithms , which allow to eliminate unwanted regions, derived from procurement methods or inadequate capture that eventually introduce some kind of noise in images. Thus, the objective is to comparatively evaluate different existing filters in order to add to the knowledge about the process of spatial filtering, since studies of this nature are still scarce in the literature. Image were used regarding the rural municipality of Frederico Westphalen, Landsat-5/TM Imager bands 3 (0.63 to 0.69 µm), 4 (0.76 to 0.90 µm) and 5 (1,55 to 1.75 µm) of the year 1985, previously georeferenced which formed the basis for the registration of the images . It was observed that filtering processes used to demonstrate the efficiency of the filter varies with the target , changing the contrast, brightness and structure are important in the understanding of deterioration caused the original image.